S22 Bap1 expression and treatment outcomes in malignant pleural mesothelioma in a prospective uk based clinical trial. (15th November 2017) - Kumar, N; Kolluri, K; Rifai, D Al; Ishii, Y; Borg, E; Falzon, M; Nicholson, A; Janes, S
Abstract : Objectives: Genomic studies of malignant pleural mesothelioma (MPM) have identified frequent mutations in the nuclear deubiquitinase BRCA Associated Protein 1 (BAP1). Previous studies have identified 100% correlation between BAP1 nuclear staining and wild type BAP1 status, pointing to immunohistochemistry (IHC) as a reliable technique to detect BAP1 molecular status. The objective of this study is to assess BAP1 expression and infer molecular status using IHC in a cohort from a prospective UK based clinical trial (MSO1). Furthermore, we aim to evaluate the effect of BAP1 status on treatment outcomes. Methods: BAP1 expression was evaluated by IHC in 79 biopsies independently by two consultant histopathologists. Cases were considered positive (wild type BAP1) if strong nuclear staining was present and negative (mutant BAP1) if absent. Results: Assessment of BAP1 expression was concordant in 77 of 79 cases (97%). BAP1 expression was negative in 66 of these 77 cases (86%). Patient characteristics and the effect of BAP1 expression on treatment outcomes are in Table 1 . Conclusions: BAP1 expression was negative in 86% of MPM tumours suggesting a high frequency of BAP1 mutations in this UK cohort. No significant differences in clinical characteristics or outcomes were noted between cases with positive or negative BAP1 expression overall. When analysed by treatment subgroup, there was a trend towards a survival benefit in cases with negative BAP1 expression (BAP1 mutants) in the ASC plus vinorelbine arm, but no statistically significant difference in outcomes within any treatment arm. We plan to further validate our findings by correlating BAP1 expression directly with BAP1 molecular status in this cohort using laser capture microdissection and sequencing.